The proscription of terrorist organisations in Australia - McGarrity, Nicola (Terrorism and political violence, 2018)
Australia has a long history of legislation enabling the proscription of organisations which pose a threat to Australian security. Such laws are by no means a post-9/11 phenomenon. However, the proscription of organisations has assumed a particularly significant place in this country’s legislative response to the threat of terrorism since the terrorist attacks in New York and Washington. The focus of this article is upon the provisions of Division 102 of the Criminal Code Act 1995 (Cth), as it is this regime which has been most commonly relied upon in practice. Whilst the nature of the threat of terrorism faced by Australia has moved through several distinct phases, the basic structure of this regime has remained substantially intact. For that reason, although this article will canvass recent legislative amendments made in response to the foreign terrorist fighters phenomenon specifically, the aim is to provide a holistic picture of the form and substance of the proscription regime in Division 102. This builds upon the pre-existing scholarship in the field by carefully analysing the lessons which can be drawn from the now quite significant number of prosecutions for terrorist organisation offences.